ANALISIS GROUND VIBRATION UNTUK MENDESAIN LERENG YANG STABIL PADA PENAMBANGAN BATU GAMPING CV TEKAD JAYA HALABAN KABUPATEN 50 KOTA SUMATERA BARAT - Halimah Halimah; Adree Octova (Departemen Teknik Pertambangan FT UNP, 2018)
Abstract. Blasting activities can cause vibrations that disrupt the surrounding environment, one of which is slope. In the planning of slopes, the magnitude of vibration due to blasting is needed to design the stable slope. To determine the effect of blasting vibration as known as horizontal vibration acceleration (amax) on slope stability then measurements of blasting vibration were taken in 10 point surrounding the location of blasting. Based on the data obtained, the parameters of seismic wave that required are frequency, peak particle velocity (PPV) dan peak particle acceleration (PPA). However, internal factors such as the physical and mechanical properties of the rocks that make up the slope are also very needed. After processing the data, the predicted value of vibration at the point of slope is 0,01531 g and after slope evaluation using Bishop and Janbu methods, the impact of vibration on the slope is around 0,07 – 0,25. The final slope design parameters consist of a single slope with a height of 38 m and the angle of slope is 900. Safe limit of vibration blasting against the slope with trial and error test is 1,9 g. Keywords: Blasting Vibration, Planning of Slope, The Parameters of Seismic Wave, Rock Tests